Ultrasound assisted miniemulsion polymerization to prepare poly(urea-urethane) nanoparticles - Polloni,André Eliezer (2018)
Abstract Recently, the physical and chemical effects of ultrasound in polymeric materials synthesis have attracted great attention. This work presents the synthesis of novel polymeric materials by polymerization of isophorone diisocyanate with different polyols. Polymers were synthesized by step miniemulsion polymerizations, using ultrasound bath and thermostatic bath. The effects of ultrasound, temperature and polyol type were evaluated by Fourier transform infrared spectroscopy, gel permeation chromatography, dynamic light scattering and titrimetry. Polymerization under ultrasound bath showed that different reaction temperatures in the range between 50 °C and 80 °C directly influence the molecular weight of the polymers, urea/urethane formation and increase of diisocyanate consumption rate. In addition, different polyols used in polymerizations in miniemulsion had a significant effect on the characteristics of the resulting poly(urea-urethane) nanoparticles. Finally, ultrasound assisted polymerizations showed a faster diisocyanate consumption rate, but did not lead to enhanced molecular weights.